Hybrid CMR- and FDG-PET-Imaging Gives New Insights Into the Relationship of Myocardial Metabolic Activity and Fibrosis in Patients With Becker Muscular Dystrophy - Vehof, Volker; Büther, Florian; Florian, Anca; Drakos, Stefanos; Chamling, Bishwas; Kies, Peter; Stegger, Lars; Yilmaz, Ali (Frontiers in Cardiovascular Medicine, 2022)
Background Cardiac involvement in patients with Becker muscular dystrophy (BMD) is an important predictor of mortality. The cardiac phenotype of BMD patients is characterized by slowly progressive myocardial fibrosis that starts in the left ventricular (LV) free wall segments and extends into the septal wall during the disease course. Purpose Since the reason for this characteristic cardiac phenotype is unknown and comprehensive approaches using e.g. hybrid imaging combining cardiovascular magnetic resonance (CMR) with 18F-fluorodeoxyglucose (FDG) positron emission tomography (PET) are limited, the present study addressed this issue by a comprehensive non-invasive imaging approach. Methods Hybrid CMR- and FDG-PET-imaging was performed in N = 14 patients with BMD on a whole-body Biograph mMR system (Siemens, Erlangen, Germany). The CMR protocol comprised cine- and late-gadolinium-enhancement (LGE)-imaging. Metabolism was assessed with FDG-PET after oral glucose loading to effect myocardial carbohydrate uptake. PET was acquired for 65 min starting with tracer injection. Uptake values from 60 to 65 min p.i. were divided by the area under the blood activity curve and reported as percentages relative to the segment with maximal myocardial FDG uptake. Results A characteristic pattern of LGE in the LV lateral wall was observed in 13/14 patients whereas an additional septal LGE pattern was documented in 6/14 patients only. There was one patient without any LGE. Segmental FDG uptake was 88 ± 6% in the LV lateral wall vs. 77 ± 10% in the septal wall (p < 0.001). There was an inverse relationship between segmental FDG activity compared to segmental LGE extent (r = −0.33, p = 0.089). There were N = 6 LGE-positive patients with a segmental difference in FDG uptake of >15% in the LV lateral wall compared to the septal wall = ΔFDG-high group (lateral FDG = 91±3% vs. septal FDG = 69±8%; p < 0.001) while the remaining N = 7 LGE-positive patients showed a segmental difference in FDG uptake of ≤ 15% = ΔFDG-low group (lateral FDG = 85±7% vs. septal FDG = 83 ± 5%; p = 0.37). Patients in the ΔFDG-high group showed only a minor difference in the LGE extent between the LV lateral wall vs. septal wall (p = 0.09) whereas large differences were observed in the ΔFDG-low group (p < 0.004). Conclusions Segmental FDG uptake—reflecting myocardial metabolic activity—is higher in the LV free wall of BMD patients—possibly due to a higher segmental work load. However, segmental metabolic activity seems to be dependent on and limited by the respective segmental extent of myocardial fibrosis as depicted by LGE-imaging.